Neoechinorhynchus Iraqenesis Helminthes Isolated from Two Freshwater Fishes Species in Umm an Ni`aj Marsh in Maysan Province, South of Iraq (Journal of Pharmaceutical Negative Results, 2022)
A total 294 fish species collected as follows; Silurus triostegus (100) and Planiliza abu (194) were collected randomly from Umm an Ni`ajmarsh during the period of sample collection Jan 2019 till Jun 2019. Neoechinorhynchus iraqenesis is the parasite belonging to the phylum acanthocephala, during current study this parasite has recorded from the intestines of S. triostegus and P. abu hosts, where the infection rate in P. abu (22%) was higher than that of S. triostegus (10%). Current study dealt mainly with the study of some morphological characteristics of the parasite in order to diagnosis, after the parasite has been dyed and examined under a light microscope.